In vitro and in vivo evaluations of the antifungal activity of salicylic acid and silicon against Ganoderma boninense - Ainnur Atira Mohammad Seri,; Dzarifah Mohamed Zulperi,; Siti Izera Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Basal stem rot disease (BSR) in oil palms is one of the primary diseases that has led to the wide use of fungicides. This increased the development of fungal isolates resistant to fungicides and led to the search for alternative strategies to replace the use of fungicides. This study aimed to evaluate in vitro antifungal activity of salicylic acid (SA) and silicon (Si) in inhibiting mycelial growth of Ganoderma boninense using Poison Food Technique and to evaluate the in vivo efficacy of Si treatment on oil palm seedlings growth and resistance towards G. boninense. Percentage inhibition of radial mycelial growth (PIRG) was assessed, and Si treatment significantly reduced mycelial radial growth of G. boninense up to 100% inhibition at concentrations of 200 and 250 mg/L. The half-maximal effective concentration (EC50 ) for Si was 68.57 mg/L, while for SiO2 , it was 273.95 mg/L. The EC50 for salicylic acid was 381.33 mg/L. For in vivo evaluation, oil palm seedlings treated with Si at 150, 200, and 250 mg/L showed the lowest severity of leaf chlorosis and necrotic symptoms, which were 7.36%, 6.49%, and 4.05%, respectively. In contrast, the seedlings without Si showed the highest severity of leaf symptoms. Examination of internal bole tissues of oil palm seedlings treated with Si at a concentration of 250 mg/L also recorded a 3.0% mean percentage of disease severity compared to the untreated infected seedlings, which showed 35.0% disease severity. Our findings demonstrated the potential of Si application in controlling the BSR disease caused by Ganoderma boninense.